Water quality of the Refugio Mata Redonda and surrounding rice paddies, Guanacaste, Costa Rica. - Pérez-Castillo, Ana Gabriela (2013)
The objective of this study was assess if the water quality from the Mata Redonda lagoon (MRL) and from the rice fields in San Lazaro sector of Nicoya, is appropriate for biodiversity and aquatic life development. The water quality analysis was carried out using the Water quality index for managing flood lagoons (ICA-L), which is based on the following data: temperature, pH, oxygen saturation percentage, electrical conductivity, biochemical oxygen demand, suspended solids, nitrate content and total phosphorus content. The ICA-L average (ICA-Lp) from the water drained form the rice fields in the main channel was 42, which corresponds to a ¨bad¨ category value (unfit for sustaining biodiversity in flood lagoons). In the MRL (ICA-Lp 80) and in the lagoon´s drainage (ICA-Lp 81), water quality was classified as “good”. Nevertheless, increases in total phosphorus and the biological oxygen demand (BOD) may cause negative changes in the composition of the ecosystem. The risk level associated with pesticide application in rice fields (under the San Lazaro area conditions during the study period) was estimated using the Pesticide Impact Rating Index (PIRI). The PIRI results showed that the less appropriate to use pesticides are: deltamethrin, esfenvalerate, permethrin and butachlor, because of their high toxicity and mobility. On the other hand, imidapropid, bispyribac-Na, triazophos, glyphosate, acephate, clomazone and tricopyr, would be less dangerous if applied under appropriate practices.